Short Wavelength Cone Opsin Is Not Expressed in the Retina of Arboreal African Pangolin (Manis tricuspis) - Adejoke J. Adekanmbi; Adefisayo A. Adekanmbi; Oluwole B. Akinola (Scientifica)
This paper reports a study of cone photoreceptors present in the retina of Manis tricuspis. Specifically, the LWS (L-) opsin expressed in longwave-sensitive cones and SWS1 (S-) opsin shortwave-sensitive cones were targeted. Vertical sections revealed reactivity to a cone marker, peanut agglutinin (PNA), and to an LWS antibody, but not to an SWS1 antibody. This suggests that the Manis tricuspis visual system is not able to discriminate shorter wavelengths from longer wavelengths because the short wavelength cones are not expressed in their retina.